CONTRIBUTION OF ANZAR SHAH KASHMIRI TO HADITH AND ISLAMIC SCIENCES - Ajmal, Mohammad; Al Rasyid, Harun (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: This research paper, has tried to highlight the contribution of Anzar Shah Kashmiri to hadith and Islamic sciences. The research concentrates on one of the prominent figures of Darul Uloom Deoband who devoted his entire life to the service of the Qur'an and Hadith, and was a teacher of Hadith and Tafsir as well as a scholar of the sciences of these two most authentic subjects in Islamic studies and research. To write this research, I read and researched many articles in Arabic and English and Urdu, from different authors about Sheikh Anzar Shah Kashmiri to complete this paper. Sheikh Anzar Shah Kashmiri was one of the great scholars of Islamic sciences in India, who through his vast knowledge of Hadith and Quranic sciences, transmitted the information to his disciples and students in particular, while through his public speeches and addresses, the information was transferred to the general public in general. Keywords : Anzar Shah Kashmiri, Hadith, Tafsir, Darul Uloom Deoband, Islamic scholars in India